Preparation method of polylactic acid porous microspheres and application of polylactic acid porous microspheres in stem cell inoculation
Polylactic acid/chitosan composite porous microspheres are prepared through a double-emulsion solvent evaporation method, which solves the problem of low biological activity of microspheres in the existing technology, achieves high-proportion cell attachment and proliferation effects, and is suitable for stem cell inoculation carriers.
Patent Information
- Application Number
- CN202411429519.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-24
AI Technical Summary
In the prior art, the bioactive glass/polylactic acid-glycolic acid copolymer composite microspheres have low biological activity and cannot meet the attachment and proliferation of high proportions of cells.
Remove the dual emulsion solvents to prepare polymapilic acid/shell polynamium porous microspheres containing biological activated glass, and use the water phase extraction process to form a uniform pore distribution and high biological activated microspheres to enhance the adsorption capacity of protein or peptide on the surface of the microsphere surface. Essence
The micro -ball distributed by higher biological activity and uniform pores can be achieved, which can meet the adhesion and proliferation of high proportional cells, and it is suitable for stem cell vaccination.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of functional composite materials, and in particular to a preparation method of polylactic acid porous microspheres and application of the microspheres in stem cell inoculation. Background Art
[0002] In tissue engineering and regenerative medicine, scaffold materials play a vital role in promoting cell attachment, proliferation and differentiation. Polylactic-co-glycolic acid (PLGA), polylactic acid (PLA) and polycaprolactone (PCL) are all biodegradable polymer materials that have been widely used in the biomedical field. By combining hydroxyapatite (HA) or bioactive glass (BAG) with PLGA, PLA or PCL, their biocompatibility and osteoconductivity can be improved. However, further promoting cell attachment and proliferation remains a challenge.
[0003] The invention patent with publication number CN 111905151 A discloses a mesoporous bioactive glass / polylactic acid-glycolic acid copolymer composite microsphere and its preparation method and application, which specifically discloses: firstly, the mesoporous bioactive glass is prepared by combining microemulsion technology with sol-gel template method, and then PLGA, Span 80, and mesoporous bioactive glass are added to dichloromethane in sequence, stirred and ultrasonically dispersed evenly to form S / O emulsion; added to the prepared polyethylene solutions W1 and W2 of different concentrations in sequence, stirred and evaporated the solvent, and washed, centrifuged, and freeze-dried to obtain. However, the biological activity of the composite microspheres prepared by this technical solution is still low, and cannot meet the attachment and proliferation of a high proportion of cells. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a method for preparing polylactic acid porous microspheres and application of the same in stem cell inoculation. Polylactic acid / chitosan composite porous microspheres containing bioactive glass are prepared by a double emulsion solvent evaporation method. The microspheres have uniform pore size distribution and higher biological activity, and the adsorption capacity of proteins or polypeptides on the surface of the microspheres is enhanced, thereby meeting the attachment and proliferation of a high proportion of cells.
[0005] The purpose of the present invention is achieved through the following technical solutions: In a first aspect, the present invention provides a method for preparing polylactic acid porous microspheres, comprising the following steps: (1) dissolving chitosan in an acetic acid aqueous solution, adding bioactive glass nanoparticles and performing ultrasonication to obtain an aqueous solution; (2) dissolving PLGA or PLA in dichloromethane and adding an emulsifier to obtain an oil phase solution; (3) adding the aqueous phase solution dropwise to the oil phase solution to obtain a water-in-oil primary emulsion; (4) adding the water-in-oil primary emulsion dropwise to the PVA aqueous solution to obtain a double emulsion; (5) The double emulsion is stirred, centrifuged, dried, and then immersed in a glutaraldehyde solution for cross-linking treatment to obtain porous microspheres.
[0006] The present invention prepares porous microspheres by double emulsion solvent evaporation method. In the primary emulsion (W / O), the water phase of chitosan and bioactive glass (BAG) is dispersed in an organic solvent containing PLGA or PLA to form a droplet structure in which water droplets are dispersed in the oil phase. Then, the water-in-oil primary emulsion is added dropwise to the PVA aqueous solution to obtain a double emulsion (W / O / W). During the emulsification and organic solvent volatilization process, the inner water phase (chitosan / BAG) gradually migrates from the system to the outer water phase to form internal pores.
[0007] This process is similar to "aqueous phase extraction". Chitosan will carry BAG nanoparticles and gradually migrate outward. Due to the subsequent volatilization of the solvent and the phase separation of the aqueous phase inside the microspheres, pores and cavities will be left in the PLGA matrix, forming a porous structure of the microspheres, while PLGA or PLA will be solidified as a structural support material. BAG nanoparticles can also be embedded in the PLGA matrix. BAG is rich in calcium ions and can release calcium ions in an aqueous environment. Calcium ions can form ionic bonds with negatively charged parts (such as carboxyl or phosphate groups) in proteins or polypeptides, thereby enhancing the adsorption capacity of proteins or polypeptides on the surface of microspheres and increasing the biological activity of microspheres. At the same time, due to the aqueous phase extraction process, chitosan will exist in the external aqueous phase and the internal aqueous phase, and will also be embedded in the PLGA or PLA matrix. Chitosan molecules can interact with PLGA or PLA, and the three-dimensional network structure formed by the molecular chain can provide support during the curing process of the microspheres to avoid the collapse of the microsphere structure caused by voids. In addition, during the evaporation of the organic solvent, the chitosan present in the external water phase will be adsorbed on the surface of the PLGA or PLA microspheres. The chitosan molecules are rich in amino groups. The modification of the chitosan molecules on the surface of the microspheres can enhance the adsorption of proteins or peptides, help to better adsorb biological molecules in the water environment, and improve the surface activity.
[0008] Chitosan is a hydrophilic material, PLGA or PLA is a hydrophobic material, and the single emulsion method (such as W / O method) is not conducive to the uniform mixing of the two materials, while the double emulsion method (W / O / W) in the present invention helps to evenly distribute chitosan in the PLGA or PLA matrix, forming a porous structure, and can also embed BAG particles into the microspheres, and improve the biological activity of the microspheres through the distribution of chitosan and BAG in the microspheres. In addition, in the single emulsion method, the porosity and pore size of the microspheres are often difficult to control, which easily leads to uneven pore size, while the double emulsion method in the present invention is more conducive to controlling the pore size and porosity through parameters, and obtaining microspheres with more uniform pore size distribution.
[0009] Preferably, in step (1), the mass concentration of the acetic acid aqueous solution is 1-2%; the ratio of the added amounts of the chitosan, bioactive glass nanoparticles and the acetic acid aqueous solution is 1-4 g: 1-2 g: 100 mL.
[0010] Preferably, in step (1), the chitosan has a deacetylation degree of 70-80%, an average molecular weight of 20-100 kDa, and a solution viscosity of 20-100 mPa·s (1% aqueous solution, w / w, 25° C.); the average particle size of the bioactive glass nanoparticles is 200-1000 nm; and the ultrasonic conditions are: 30-50 kHz, 20-30 min.
[0011] The deacetylation degree of chitosan is 70-80%, with good hydrophilicity and biocompatibility, and it will be suspended in a dilute acetic acid solution in a flocculated state, which is conducive to the adsorption of bioactive glass nanoparticles, and is conducive to better formation of oil-in-water primary emulsions, and can escape better. If the deacetylation degree is too high, it will be dissolved in a dilute acetic acid solution in an oily state and will aggregate at the oil-water interface, which is not conducive to the escape of chitosan during aqueous phase extraction. The molecular weight of chitosan will also affect the aqueous phase extraction process. If the molecular weight is too large, the viscosity will be too large. The appropriate viscosity helps to be evenly dispersed in the aqueous phase, ensuring the stability and escape of the emulsification process, and the appropriate molecular weight can provide good mechanical strength and good solubility, which helps the formation of pores.
[0012] Preferably, in step (2), the ratio of the added amount of PLGA or PLA to dichloromethane is 4-6 g:500 mL; and the average molecular weight of the PLGA or PLA is 10-50 kDa.
[0013] Preferably, in step (2), the emulsifier is PVA or Tween 80; and the oil phase solution contains 1 to 5 g / mL of the emulsifier.
[0014] Preferably, in step (3), the volume ratio of the aqueous phase solution to the oil phase solution is 1 to 1.3:5.
[0015] Preferably, in step (3), the aqueous phase solution is added dropwise to the oil phase solution, and stirring and ultrasound are performed simultaneously; the stirring conditions are: 1000-1500 rpm, 30-40 min; the ultrasound conditions are: 30-50 kHz, 20-30 min.
[0016] Preferably, in step (4), the concentration of the PVA aqueous solution is 10-12 g / L; and the volume ratio of the water-in-oil primary emulsion to the PVA aqueous solution is 6-8:50.
[0017] Preferably, in step (4), the water-in-oil colostrum is added dropwise to the PVA aqueous solution while stirring; the stirring conditions are: 600-800 rpm, 60-90 min.
[0018] The porosity and pore size of the microspheres can be adjusted by adjusting the water-oil ratio, stirring speed, and solvent evaporation time. The ratio of the aqueous phase to the oil phase directly affects the porosity and pore size. A high aqueous phase ratio will lead to the formation of more pores, affecting the mechanical properties and structural stability of the microspheres. A low aqueous phase ratio may lead to fewer pores, affecting the effect of stem cell inoculation. The stirring speed will affect the emulsification effect and the size of the microspheres, thereby affecting the structural stability of the microspheres. The rate of solvent evaporation affects the rate of PLGA / PLA curing and the effect of aqueous phase extraction. The appropriate evaporation rate is conducive to the formation of a uniform pore structure, the internal aqueous phase has sufficient migration time, and chitosan can be better modified on the surface of PLGA or PLA microspheres.
[0019] Preferably, in step (5), the double emulsion is stirred at room temperature to promote the volatilization of dichloromethane, during which PLGA or PLA is gradually solidified to form PLGA or PLA microspheres with a porous structure; the microspheres are separated by centrifugation and then washed with deionized water to remove residual PVA and solvent; the washed microspheres are freeze-dried, and the dried microspheres are immersed in a glutaraldehyde solution for cross-linking treatment, and then washed and dried again to obtain porous microspheres.
[0020] Freeze drying can be used to further remove water from the microspheres to prevent the pore structure from collapsing during the subsequent drying process. During the freeze drying process, the sublimation of water will leave more pores and help maintain the porous network structure inside the microspheres. Compared with conventional drying methods, freeze drying can better maintain the porosity and pore size distribution of the microspheres.
[0021] Glutaraldehyde can cross-link with chitosan molecules on the surface of porous microspheres, improve the mechanical strength of the porous microspheres, make them more stable and resistant to swelling in a wet environment, and thus help maintain the structural integrity of the microspheres.
[0022] Preferably, in step (5), the stirring conditions at room temperature are: 400-500 rpm, 12-14 h; the centrifugal separation conditions are 3000-5000 rpm, 10-20 min; and the freeze-drying is drying at -20--30°C for 24-48 h.
[0023] Preferably, in step (5), the mass concentration of the glutaraldehyde solution is 0.5-1%; and the time of the cross-linking treatment is 40-60 minutes.
[0024] In a second aspect, the present invention also provides a use of the porous microspheres prepared by the above preparation method in stem cell inoculation, wherein the porous microspheres serve as stem cell inoculation carriers.
[0025] The porous microspheres prepared by the present invention have more uniform pore size distribution and higher biological activity, and enhance the adsorption capacity of proteins or polypeptides on the surface of the microspheres, so that they can be used as excellent stem cell inoculation carriers to meet the attachment and proliferation of a high proportion of cells.
[0026] Preferably, the porous microspheres are surface functionalized before being used as stem cell inoculation carriers. The surface functionalization step includes: immersing the dried porous microspheres in an aqueous solution containing a hydroxyl active agent or an amino active agent for activation treatment, transferring the activated microspheres to an aqueous solution containing extracellular matrix proteins or polypeptides for incubation, and then centrifuging.
[0027] Preferably, in the aqueous solution containing a hydroxyl active agent or an amino active agent, the concentration of the active agent is 1 to 5 mg / mL; the conditions for the activation treatment are: a temperature of 4°C or room temperature, and a time of 1 to 2 hours; in the aqueous solution containing an extracellular matrix protein or a polypeptide, the concentration of the extracellular matrix protein is 0.1 to 1 mg / mL, and the concentration of the polypeptide is 0.01 to 0.1 mg / mL; and the conditions for the incubation are: a temperature of 4°C or room temperature, and a time of 12 to 24 hours.
[0028] Preferably, the surface functionalized microspheres are dispersed in a suspension of mesenchymal stem cells (MSCs) or osteoblasts at a cell concentration of 1×10 5 ~1×10 6 cells / mL, incubate with gentle stirring or shaking for 2-4 h at 37°C and 5% CO2.
[0029] Compared with the prior art, the present invention has the following beneficial effects: (1) The porous microspheres were prepared by double emulsion solvent evaporation method. While improving the uniformity of the dispersion of bioactive glass and chitosan in the polylactic acid matrix, the porosity and pore size of the microspheres can be adjusted by adjusting the water-oil ratio, stirring speed and solvent evaporation time. (2) Porous microspheres have a more uniform pore size distribution and higher biological activity, which enhances the adsorption capacity of proteins or peptides on the surface of the microspheres, making them excellent stem cell inoculation carriers that can meet the needs of high-proportion cell attachment and proliferation. DETAILED DESCRIPTION
[0030] The technical solution of the present invention is described below with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0031] Example 1 1. Preparation of polylactic acid porous microspheres containing bioactive glass: (1) Dissolve 2 g of chitosan (with a degree of deacetylation of 80% and a viscosity of 80 mPa·s) in 100 mL of 1% acetic acid aqueous solution and stir until completely dissolved. Add 1 g of bioactive glass nanoparticles (average particle size of 500 nm) and treat them with an ultrasonic processor at 40 kHz for 20 min to uniformly disperse them in the chitosan solution to obtain an aqueous phase solution.
[0032] (2) 5 g of PLGA (average molecular weight 30 kDa) was dissolved in 500 mL of dichloromethane and stirred until completely dissolved. An emulsifier (Tween 80) was added and stirred evenly to obtain an oil phase solution containing 2 g / mL of emulsifier.
[0033] (3) The aqueous phase solution was slowly added dropwise to the oil phase solution while stirring at 1000 rpm for 30 min and ultrasonically treated at 40 kHz to form a uniform water-in-oil (W / O) primary emulsion.
[0034] (4) 50 g of polyvinyl alcohol was dissolved in 5 L of deionized water to obtain a polyvinyl alcohol aqueous solution. The water-in-oil (W / O) primary emulsion was slowly added dropwise to the polyvinyl alcohol aqueous solution while stirring at 800 rpm for 60 min to form a water-in-oil-in-water (W / O / W) double emulsion.
[0035] (5) The double emulsion was stirred at 500 rpm for 12 h at room temperature to form PLGA microspheres with a porous structure. The microspheres were separated by centrifugation at 3000 rpm for 15 min, and then washed with deionized water for 3 times, 5 L each time, and the washed microspheres were freeze-dried at -30°C for 24 h.
[0036] (6) The dried microspheres were immersed in a glutaraldehyde solution with a mass concentration of 0.5% for cross-linking treatment for 1 hour, and then washed and dried again to obtain porous microspheres.
[0037] 2. Surface functionalization of porous microspheres (protein / peptide adsorption): (1) The dried porous microspheres were immersed in a solution containing 3 mg / mL hydroxyl active agent (3-aminopropyltriethoxysilane APTES, Sigma-Aldrich 440140) to activate the surface activity. The immersion time was 2 h at a temperature of 4 °C.
[0038] (2) The activated microspheres were transferred to a solution containing 0.5 mg / mL extracellular matrix protein (collagen type I collagen, Sigma-Aldrich's Bovine Type I Collagen C9785), and gently stirred to allow uniform adsorption. The incubation time was 18 h at 4°C.
[0039] (3) After incubation, the microspheres are recovered by centrifugation or filtration and washed multiple times with PBS (phosphate buffered saline) to remove unadsorbed proteins.
[0040] 3. Stem cell inoculation: (1) The surface functionalized microspheres were dispersed in a mesenchymal stem cell suspension with a cell concentration of 4.8×10^5 cells / mL.
[0041] (2) Incubate the microsphere and cell mixture on a shaker for 3 h at 37° C. and 5% CO 2 .
[0042] Example 2 1. Preparation of polylactic acid porous microspheres containing bioactive glass: (1) 3 g of chitosan (with a degree of deacetylation of 80% and a viscosity of 80 mPa·s) was dissolved in 100 mL of 1% acetic acid aqueous solution and stirred until completely dissolved. 1.6 g of bioactive glass nanoparticles (average particle size of 500 nm) were added and treated with an ultrasonic processor at 40 kHz for 30 min to uniformly disperse them in the chitosan solution to obtain an aqueous phase solution.
[0043] (2) 5 g of PLGA (average molecular weight 30 kDa) was dissolved in 500 mL of dichloromethane and stirred until completely dissolved. An emulsifier (Tween 80) was added and stirred evenly to obtain an oil phase solution containing 2 g / mL of emulsifier.
[0044] (3) The aqueous phase solution was slowly added dropwise to the oil phase solution while stirring at 1200 rpm for 40 min and ultrasonically treated at 40 kHz to form a uniform water-in-oil (W / O) primary emulsion.
[0045] (4) 50 g of polyvinyl alcohol was dissolved in 5 L of deionized water to obtain a polyvinyl alcohol aqueous solution. The water-in-oil (W / O) primary emulsion was slowly added dropwise to the polyvinyl alcohol aqueous solution while stirring at 800 rpm for 90 min to form a water-in-oil-in-water (W / O / W) double emulsion.
[0046] (5) The double emulsion was stirred at 400 rpm for 14 h at room temperature to form PLGA microspheres with a porous structure. The microspheres were separated by centrifugation at 3000 rpm for 15 min, and then washed with deionized water for 3 times, 5 L each time, and the washed microspheres were freeze-dried at -30°C for 24 h.
[0047] (6) The dried microspheres were immersed in a glutaraldehyde solution with a mass concentration of 0.8% for cross-linking treatment for 50 min, and then washed and dried again to obtain porous microspheres.
[0048] 2. Surface functionalization of porous microspheres (protein / peptide adsorption): (1) The dried porous microspheres were immersed in a solution containing 3 mg / mL hydroxyl active agent (3-aminopropyltriethoxysilane APTES, Sigma-Aldrich 440140) to activate the surface activity. The immersion time was 2 h at a temperature of 4 °C.
[0049] (2) The activated microspheres were transferred to a solution containing 0.5 mg / mL extracellular matrix protein (collagen type I collagen, Sigma-Aldrich's Bovine Type I Collagen C9785), and gently stirred to allow uniform adsorption. The incubation time was 18 h at 4°C.
[0050] (3) After incubation, the microspheres are recovered by centrifugation or filtration and washed multiple times with PBS (phosphate buffered saline) to remove unadsorbed proteins.
[0051] 3. Stem cell inoculation: (1) The surface functionalized microspheres were dispersed in a mesenchymal stem cell suspension with a cell concentration of 4.8×10^5 cells / mL.
[0052] (2) Incubate the microsphere and cell mixture on a shaker for 3 h at 37° C. and 5% CO 2 .
[0053] Example 3 1. Preparation of polylactic acid porous microspheres containing bioactive glass: (1) 4 g of chitosan (with a degree of deacetylation of 80% and a viscosity of 80 mPa·s) was dissolved in 100 mL of an aqueous solution of 2% acetic acid and stirred until completely dissolved. 2 g of bioactive glass nanoparticles (average particle size of 500 nm) were added and treated with an ultrasonic processor at 40 kHz for 30 min to uniformly disperse them in the chitosan solution to obtain an aqueous phase solution.
[0054] (2) 6 g of PLGA (average molecular weight 30 kDa) was dissolved in 500 mL of dichloromethane and stirred until completely dissolved. An emulsifier (Tween 80) was added and stirred evenly to obtain an oil phase solution containing 3 g / mL of emulsifier.
[0055] (3) The aqueous phase solution was slowly added dropwise to the oil phase solution while stirring at 1000 rpm for 30 min and ultrasonically treated at 40 kHz to form a uniform water-in-oil (W / O) primary emulsion.
[0056] (4) 60 g of polyvinyl alcohol was dissolved in 5 L of deionized water to obtain a polyvinyl alcohol aqueous solution. The water-in-oil (W / O) primary emulsion was slowly added dropwise to the polyvinyl alcohol aqueous solution while stirring at 800 rpm for 60 min to form a water-in-oil-in-water (W / O / W) double emulsion.
[0057] (5) The double emulsion was stirred at 400 rpm for 14 h at room temperature to form PLGA microspheres with a porous structure. The microspheres were separated by centrifugation at 3000 rpm for 15 min, and then washed with deionized water for 3 times, 5 L each time, and the washed microspheres were freeze-dried at -30°C for 24 h.
[0058] (6) The dried microspheres were immersed in a glutaraldehyde solution with a mass concentration of 0.5% for cross-linking treatment for 1 hour, and then washed and dried again to obtain porous microspheres.
[0059] 2. Surface functionalization of porous microspheres (protein / peptide adsorption): (1) The dried porous microspheres were immersed in a solution containing 3 mg / mL hydroxyl active agent (3-aminopropyltriethoxysilane APTES, Sigma-Aldrich 440140) to activate the surface activity. The immersion time was 2 h at a temperature of 4 °C.
[0060] (2) The activated microspheres were transferred to a solution containing 0.5 mg / mL extracellular matrix protein (collagen type I collagen, Sigma-Aldrich's Bovine Type I Collagen C9785), and gently stirred to allow uniform adsorption. The incubation time was 18 h at 4°C.
[0061] (3) After incubation, the microspheres are recovered by centrifugation or filtration and washed multiple times with PBS (phosphate buffered saline) to remove unadsorbed proteins.
[0062] 3. Stem cell inoculation: (1) The surface functionalized microspheres were dispersed in a mesenchymal stem cell suspension with a cell concentration of 4.8×10^5 cells / mL.
[0063] (2) Incubate the microsphere and cell mixture on a shaker for 3 h at 37° C. and 5% CO 2 .
[0064] Comparative Example 1 The difference from Example 1 is that chitosan is not added during the preparation of the polylactic acid porous microspheres.
[0065] (1) 1 g of bioactive glass nanoparticles (average particle size 500 nm) was added to 100 mL of aqueous solution and treated with an ultrasonic processor at 40 kHz for 20 min to obtain an aqueous solution.
[0066] (2) 5 g of PLGA (average molecular weight 30 kDa) was dissolved in 500 mL of dichloromethane and stirred until completely dissolved. An emulsifier (Tween 80) was added and stirred evenly to obtain an oil phase solution containing 2 g / mL of emulsifier.
[0067] (3) The aqueous phase solution was slowly added dropwise to the oil phase solution while stirring at 1000 rpm for 30 min and ultrasonically treated at 40 kHz to form a uniform water-in-oil (W / O) primary emulsion.
[0068] (4) 50 g of polyvinyl alcohol was dissolved in 5 L of deionized water to obtain a polyvinyl alcohol aqueous solution. The water-in-oil (W / O) primary emulsion was slowly added dropwise to the polyvinyl alcohol aqueous solution while stirring at 800 rpm for 60 min to form a water-in-oil-in-water (W / O / W) double emulsion.
[0069] (5) The double emulsion was stirred at 500 rpm for 12 h at room temperature to form PLGA microspheres with a porous structure. The microspheres were separated by centrifugation at 3000 rpm for 15 min, and then washed with deionized water for 3 times, 5 L each time, and the washed microspheres were freeze-dried at -30°C for 24 h.
[0070] (6) The dried microspheres were immersed in a glutaraldehyde solution with a mass concentration of 0.5% for cross-linking treatment for 1 hour, and then washed and dried again to obtain porous microspheres.
[0071] Comparative Example 2 The difference from Example 1 is that during the preparation of the polylactic acid porous microspheres, the concentration of chitosan in the acetic acid aqueous solution is too high.
[0072] (1) Dissolve 5 g of chitosan (with a degree of deacetylation of 80% and a viscosity of 80 mPa·s) in 100 mL of 1% acetic acid aqueous solution and stir until completely dissolved. Add 1 g of bioactive glass nanoparticles (average particle size of 500 nm) and treat them with an ultrasonic processor at 40 kHz for 20 min to uniformly disperse them in the chitosan solution to obtain an aqueous phase solution.
[0073] (2) 5 g of PLGA (average molecular weight 30 kDa) was dissolved in 500 mL of dichloromethane and stirred until completely dissolved. An emulsifier (Tween 80) was added and stirred evenly to obtain an oil phase solution containing 2 g / mL of emulsifier.
[0074] (3) The aqueous phase solution was slowly added dropwise to the oil phase solution while stirring at 1000 rpm for 30 min and ultrasonically treated at 40 kHz to form a uniform water-in-oil (W / O) primary emulsion.
[0075] (4) 50 g of polyvinyl alcohol was dissolved in 5 L of deionized water to obtain a polyvinyl alcohol aqueous solution. The water-in-oil (W / O) primary emulsion was slowly added dropwise to the polyvinyl alcohol aqueous solution while stirring at 800 rpm for 60 min to form a water-in-oil-in-water (W / O / W) double emulsion.
[0076] (5) The double emulsion was stirred at 500 rpm for 12 h at room temperature to form PLGA microspheres with a porous structure. The microspheres were separated by centrifugation at 3000 rpm for 15 min, and then washed with deionized water for 3 times, 5 L each time, and the washed microspheres were freeze-dried at -30°C for 24 h.
[0077] (6) The dried microspheres were immersed in a glutaraldehyde solution with a mass concentration of 0.5% for cross-linking treatment for 1 hour, and then washed and dried again to obtain porous microspheres.
[0078] Comparative Example 3 The difference from Example 1 is that during the preparation of the polylactic acid porous microspheres, the amount of the internal water phase added is too much relative to the oil phase.
[0079] (1) 3 g of chitosan (with a deacetylation degree of 80% and a viscosity of 80 mPa·s) was dissolved in 150 mL of 1% acetic acid aqueous solution and stirred until completely dissolved. 1.5 g of bioactive glass nanoparticles (average particle size of 500 nm) was added and treated with an ultrasonic processor at 40 kHz for 30 min to uniformly disperse the bioactive glass nanoparticles in the chitosan solution to obtain an aqueous phase solution.
[0080] (2) 5 g of PLGA (average molecular weight 30 kDa) was dissolved in 500 mL of dichloromethane and stirred until completely dissolved. An emulsifier (Tween 80) was added and stirred evenly to obtain an oil phase solution containing 2 g / mL of emulsifier.
[0081] (3) The aqueous phase solution was slowly added dropwise to the oil phase solution while stirring at 1000 rpm for 30 min and ultrasonically treated at 40 kHz to form a uniform water-in-oil (W / O) primary emulsion.
[0082] (4) 50 g of polyvinyl alcohol was dissolved in 5 L of deionized water to obtain a polyvinyl alcohol aqueous solution. The water-in-oil (W / O) primary emulsion was slowly added dropwise to the polyvinyl alcohol aqueous solution while stirring at 800 rpm for 60 min to form a water-in-oil-in-water (W / O / W) double emulsion.
[0083] (5) The double emulsion was stirred at 500 rpm for 12 h at room temperature to form PLGA microspheres with a porous structure. The microspheres were separated by centrifugation at 3000 rpm for 15 min, and then washed with deionized water for 3 times, 5 L each time, and the washed microspheres were freeze-dried at -30°C for 24 h.
[0084] (6) The dried microspheres were immersed in a glutaraldehyde solution with a mass concentration of 0.5% for cross-linking treatment for 1 hour, and then washed and dried again to obtain porous microspheres.
[0085] Comparative Example 4 The difference from Example 1 is that during the preparation of the polylactic acid porous microspheres, the stirring speed of the solvent volatilization is too fast and the volatilization time is too short.
[0086] (1) Dissolve 2 g of chitosan (with a degree of deacetylation of 80% and a viscosity of 80 mPa·s) in 100 mL of 1% acetic acid aqueous solution and stir until completely dissolved. Add 1 g of bioactive glass nanoparticles (average particle size of 500 nm) and treat them with an ultrasonic processor at 40 kHz for 20 min to uniformly disperse them in the chitosan solution to obtain an aqueous phase solution.
[0087] (2) 5 g of PLGA (average molecular weight 30 kDa) was dissolved in 500 mL of dichloromethane and stirred until completely dissolved. An emulsifier (Tween 80) was added and stirred evenly to obtain an oil phase solution containing 2 g / mL of emulsifier.
[0088] (3) The aqueous phase solution was slowly added dropwise to the oil phase solution while stirring at 1000 rpm for 30 min and ultrasonically treated at 40 kHz to form a uniform water-in-oil (W / O) primary emulsion.
[0089] (4) 50 g of polyvinyl alcohol was dissolved in 5 L of deionized water to obtain a polyvinyl alcohol aqueous solution. The water-in-oil (W / O) primary emulsion was slowly added dropwise to the polyvinyl alcohol aqueous solution while stirring at 800 rpm for 60 min to form a water-in-oil-in-water (W / O / W) double emulsion.
[0090] (5) The double emulsion was stirred at 1000 rpm for 6 h at room temperature to form PLGA microspheres with a porous structure. The microspheres were separated by centrifugation at 3000 rpm for 15 min, and then washed with deionized water for 3 times, 5 L each time, and the washed microspheres were freeze-dried at -30°C for 24 h.
[0091] (6) The dried microspheres were immersed in a glutaraldehyde solution with a mass concentration of 0.5% for cross-linking treatment for 1 hour, and then washed and dried again to obtain porous microspheres.
[0092] The particle size, pore size and porosity of the porous microspheres prepared in Examples 1-3 and Comparative Examples 1-4 were measured. After the surface-functionalized porous microspheres were inoculated with stem cells, the proliferation rate of the stem cells inoculated on the microspheres was detected and calculated using a CCK-8 kit (Cell Counting Kit-8). The stem cell proliferation rate = the number of stem cells after inoculation 72 hours / the number of stem cells at the initial inoculation * 100%. The results are shown in Table 1.
[0093] Table 1 Average particle size / μm Average pore size / μm Porosity / % Stem cell proliferation rate / % Example 1 163 33 75 162 Example 2 188 21 88 184 Example 3 139 27 84 176 Comparative Example 1 154 25 66 138 Comparative Example 2 167 40 92 156 Comparative Example 3 169 37 93 151 Comparative Example 4 165 31 63 144 As shown in Table 1, the porous microspheres prepared by the double emulsion solvent evaporation method have higher biological activity and enhance the adsorption capacity of proteins or peptides on the surface of the microspheres, so that they can serve as excellent stem cell inoculation carriers. In addition, the microspheres have a porosity and pore size that are more suitable for stem cell inoculation and can meet the attachment and proliferation of a high proportion of cells.
[0094] Comparative Examples 1-2 show that the addition of chitosan can play a structural support role on the one hand, as the main polymer component, to form a stable porous network, and on the other hand, it helps cell adhesion and proliferation. When chitosan is not added in Comparative Example 1, although a porous structure can be formed, the porosity will be reduced, the pore size uniformity will also be reduced, and the structural stability will be reduced, and the biological activity of the microspheres will also be reduced, so that the stem cell proliferation rate will be significantly reduced. In Comparative Example 2, the excessive concentration of chitosan will also be unfavorable for the formation of a suitable porous structure, and the pore size is too large and the distribution is too much, which will cause the pores to collapse, which is not conducive to high-proportion stem cell inoculation, and the stem cell proliferation rate is reduced.
[0095] Similarly, in Comparative Example 3, the proportion of the internal water phase is too large, which will lead to the generation of more pores, the structure of the microspheres is unstable, and it will be unfavorable for high-ratio stem cell inoculation. In Comparative Example 4, the stirring speed in the solvent volatilization process is too fast, and the volatilization time is too short. The water phase does not have enough time to migrate and escape from the microspheres, which will be unfavorable for obtaining a uniform pore distribution during the water phase extraction process, and will result in a low porosity, which is also unfavorable for high-ratio stem cell inoculation.
[0096] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the specification of the present invention, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing polylactic acid porous microspheres, characterized in that: The steps include: (1) Dissolving chitosan in an acetic acid aqueous solution, adding bioactive glass nanoparticles and then sonicating to obtain an aqueous solution; (2) dissolving PLGA or PLA in dichloromethane and adding an emulsifier to obtain an oil phase solution; (3) adding the aqueous phase solution dropwise to the oil phase solution to obtain a water-in-oil primary emulsion; (4) adding the water-in-oil primary emulsion dropwise into the PVA aqueous solution to obtain a double emulsion; (5) The double emulsion is stirred, centrifuged, dried, and then immersed in a glutaraldehyde solution for cross-linking treatment to obtain porous microspheres.
2. The method for preparing polylactic acid porous microspheres according to claim 1, characterized in that: In step (1), the mass concentration of the acetic acid aqueous solution is 1-2%; the ratio of the added amounts of chitosan, bioactive glass nanoparticles and acetic acid aqueous solution is 1-4 g: 1-2 g: 100 mL.
3. The method for preparing polylactic acid porous microspheres according to claim 1, characterized in that: In step (1), the chitosan has a deacetylation degree of 70-80% and a viscosity of 20-100 mPa·s; and the average particle size of the bioactive glass nanoparticles is 200-1000 nm.
4. The method for preparing polylactic acid porous microspheres according to claim 1, 2 or 3, characterized in that: In step (2), the ratio of the added amount of PLGA or PLA to dichloromethane is 4-6 g:500 mL; and the average molecular weight of the PLGA or PLA is 10-50 kDa.
5. The method for preparing polylactic acid porous microspheres according to claim 1, characterized in that: In step (3), the volume ratio of the aqueous phase solution to the oil phase solution is 1-1.3:
5.
6. The method for preparing polylactic acid porous microspheres according to claim 1 or 5, characterized in that: In step (4), the concentration of the PVA aqueous solution is 10-12 g / L; and the volume ratio of the water-in-oil primary emulsion to the PVA aqueous solution is 6-8:
50.
7. The method for preparing polylactic acid porous microspheres according to claim 1, characterized in that: In step (5), the stirring conditions are: 400-500 rpm, 12-14 h.
8. The method for preparing polylactic acid porous microspheres according to claim 1 or 7, characterized in that: In step (5), the mass concentration of the glutaraldehyde solution is 0.5-1%; and the time of the cross-linking treatment is 40-60 minutes.
9. Use of the porous microspheres prepared by the preparation method according to any one of claims 1 to 8 in stem cell inoculation, characterized in that: The porous microspheres are used as stem cell seeding carriers.
10. The use according to claim 9, characterized in that: Before the porous microspheres are used as stem cell inoculation carriers, surface functionalization is first performed. The surface functionalization steps include: immersing the dried porous microspheres in an aqueous solution containing a hydroxyl active agent or an amino active agent for activation treatment, then transferring the activated microspheres to an aqueous solution containing extracellular matrix proteins or polypeptides for incubation, and then centrifuging.
Citation Information
Patent Citations
Mesoporous bioactive glass / polylactic acid-glycolic acid copolymer composite microspheres and preparation method and application thereof
CN111905151A
Cited By
Green environment-friendly heat-resistant photovoltaic cable and preparation method thereof
CN119798887A
Preparation method for polylactic acid porous microspheres and use thereof in stem cell seeding
WO2026081411A1